Fuzzy logic based adaptive MPSoC for balanced energy and throughput - Adeel Ahmad; Muhammad Yasir Qadri; Nadia N. Qadri (Kuwait Journal of Science)
In this paper a Fuzzy logic based Controller has been proposed to reconfigure multi-processor system on chip (MPSoC)architecture according to the workload requirements. Mamdani and Sugeno Inference Engines are compared andanalyzed to enhance the smooth regulation of reconfiguration in design space. The proposed MPSoC platform consistsof 16 cores, where each core has private L1 cache and a shared L2 cache. The design space exploration parametersevaluated are CPUs operating frequency, number of cores, throughput and energy consumption. Marssx86 simulatoris used to build the target machine and SPLASH-2 benchmarks are executed on this configured architecture. MamdaniInference Engine for the said implementation has shown up to 14%-23% decrease in Energy-Delay2Product (ED2P) forvarious benchmark applications. Hence the performance of Mamdani inference engine was found to be better than theSugeno one for this particular implementation.